A preliminary study on timebanking awareness in Malaysia - Awang Abu Bakar, Normi Sham; Yahya, Norzariyah; Nordin, Azlin; Sheikh Abdul Aziz, Madihah (UiTM Press, 2024)
The timebanking concept has been introduced to benefit from the service exchange between the service provider and requester. In essence, this concept eliminates fiat money as a payment mechanism, and the currency used is the hour the participants used to complete a task. Apart from its implementation in several other countries, the concept of timebanking is still fairly new in our communities. Thus, a user awareness survey was conducted to investigate the level of awareness of the timebanking concept among the members of the society, and also the level of willingness to participate in the timebank system. The results show that 51% of the participants assert that they are aware of the concept of a timebank. In addition, 86% of the participants stated they were willing to participate in the timebanking project. These encouraging results show that there is a possibility that the timebank concept will be acceptable to Malaysian communities in general